Pengaruh Komunikasi Pemerintahan Ridwan Kamil Dalam Membangun Personal Branding di Social Media Tiktok dan Instagram - Galih Akbar Ramadhan; Ana Fitriana; Nurkinan Nurkinan (Peneliti.net, 2022)
Research on the influence of Ridwan Kamil's government communication in building personal branding on social media tiktok and instagram has the aim of studying and analyzing the influence of using social media tiktok and instagram in building personal branding from the figure of Ridwan Kamil as the head of the provincial government or the governor of West Java being studied. through the facts that can build personal branding according to Montoya in which there are four dimensional variables, including leadership, personality, differences and looks. This study used descriptive qualitative method. The results of this study indicate that Ridwan Kamil's leadership variable is able to make social media a place for him to carry out transparency of government administration activities to the public, Ridwan Kamil's personality dimension can be judged to be able to balance positive things about his personality to be known by the public, the difference dimension lies in jokes or jokes. His jokes in answering questions in the comments column and dimensions are seen by Ridwan Kamil sharing information, communication, and happiness with the people he leads